Corruption determinants in developing and transition economies: Insights from a multi-level analysis - Joël Cariolle (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper re-examines the contribution of five major corruption determinants emphasized by the literature, through an empirical analysis based on a hierarchical modelling of firm-level corruption data. Exploiting a baseline sample of 34,358 bribe reports of firms from 71 developing and transition countries, I use a three-level estimation framework to study the contribution of the economic and human development levels, the size of governments, trade openness, and democracy. Multi-level estimations stress that the negative effect of income per capita on bribery is found to be mostly driven by improvement in human capital, more particularly by the decline in fertility rates. They also allow the reconciling of some contrasting findings of the literature on other corruption determinants, but point that the contribution of corruption determinants is context-dependent.
Keywords: D73; D02; D22; P48; O57; 330; corruption; bribery; firm; multi-level model; hierarchical model